An atypical presentation of erythema elevatum diutinum - Tubone, Mariana Quirino; Escobar, Gabriela Fortes; Peruzzo, Juliano; Maldonado, Gabriela (Clinical and Biomedical Research, 2013)
Erythema elevatum diutinum is a rare chronic leukocytoclastic vasculitis of unknown etiology. Lesions are usually asymptomatic, although burning and itchiness can occur. The typical clinical presentation is characterized by persistent, symmetrical, papules and nodules that may coalesce to form larger nodules or plaques. It may be associated with various pathologies and the diagnosis is based on clinical and histopathological findings. Treatment is based on the use of dapsone and sulfonamides, first-line therapies, and other options such as niacinamide, tetracycline, colchicine, chloroquine and corticosteroids. We describe the case of a 65-year-old male patient that presented a single lesion on the dorsum of the hand, an unusual clinical presentation.